Educação, mediação, justiça, paz – estudos interdisciplinares: do pacto do silêncio ao pacto do diálogo - Albuquerque, Juliana Gonçalves (2021)
This research is founded on critical philosophy in an attempt to understand society, education and justice. The structure of the investigative work has as its epistemological foundation the legal sciences and education, as a path and promotion of counterculture, in the perspective of social pacification, the dignity of the human person and Universal Human Rights. A tireless seeker, she starts from the premise that the rules of the law are not enough to cover the announced problem, which requires analyzes that consider historical aspects of attitude and interdisciplinary understanding of Brazilian education, in order to unveil a possible path to rethink the concepts of citizenship and democracy in the exercise of dialogue and mediation, as an experience. The work: Education in the 60s – The pact of silence (FAZENDA, 1985), constitutes the triggering reference of this study for its critical analyzes on the favoring of technical education and the rhetoric of maintenance of the consumerist status quo, which makes the construction of citizens as critical historical subjects. Given this context, the objective of this Dissertation is to investigate dialogue as a mediation of speech as an expression of the historical-critical subject and, therefore, constructor/transformer of its reality, aiming to promote a new sociability based on the values of participatory citizenship , compassionate and peaceful, mediated by a dialogic pedagogy, as a constituent of his speech in the world, in the perspective of revolutionizing the current latent logic, which is based on a moralizing duality of relationships, hierarchizing knowledge and relationships of real and symbolic violence. The theoretical foundation supported, notably, in Apple (1997; 2011), Barthes (1993), Benjamin (1987), Bohm (2005), Fazenda (1985; 2002; 2003; 2012; 2015), Freire (1987; 2000; 2002) ; 2009), Gusdorf (1977) Morin (2000; 2003), Saviani (2009), Warat (2001), is consistent with the support and development of the research. The methodology used is a qualitative approach with research instruments such as literature review, document analysis and life history. It is intended that the research contributes to the solidification of the curricular path of dialogic education in the perspective of building a democratic, inclusive, integral citizenship, disseminating the mediation of conflicts, beyond the judiciary, making the citizen the builder of the value of justice